1. Rewrite the equation in the form: y = x - 4 This has slope m = 1, so any line parallel to it will have the same slope, so it will look like y = x + k where k is a constant. To find k, use the fact that it goes through point (-6, -1). i.e. you get k from: -1 = 1*(-6) + k.
2. Rewrite the equation in the form: y = -x/3 - 2. This has slope m = -1/3. Any line perpendicular to this has slope equal to -1/m. Again get the constant by substituting the specified point value to the perpendicular equation y = (-1/m)*x + k.